Bogor Botanical Gardens (Kebun Raya Bogor/KRB) has a long history of medicinal plants conservation. In order to improve the quality of the medicinal plant collections and its uses, KRB need to manage relevant on public and visitor expectation and key aspects of medicinal plant conservation. This study aims to establish the KRB management strategy for the medicinal plants collection. A set of questionnaires used in this study. The data were processed using the Likert scale, scoring, and the AH - Syamsul Hidayat; Ervizal A.M. Zuhud; Didik Widyatmoko (Forum Pasca Sarjana, 2011)
Bogor Botanical Gardens (Kebun Raya Bogor/KRB) has a long history of medicinal plants conservation.    In order to improve the quality of the medicinal plant collections and its uses, KRB need to manage relevant on public and visitor expectation and key aspects of medicinal plant conservation. This study aims to establish the KRB management strategy for the medicinal plants collection. A set of questionnaires used in this study. The data were processed using the Likert scale, scoring, and the AHP (analytic hierarchy process). The study suggested a total of 60 species that need more attention. Of the 60 species assessed 9 species were prioritised including Anaxagorea javanica, Coscinium fenestratum, Eusideroxylon zwageri, Heritiera littoralis, Kadsura scandens, Santalum album, Lunasia amara, Scorodocarpus borneensis, and Terminalia bellirica.  Three basic conservation aspects  (tri-stimulus amar)  and the key KRB functions need to be strengthened and established and yet to be in line with the public expectation in order to achieve an integrated medicinal plant ex situ conservation.  Key words: public expectation, integrated conservation, Bogor Botanical Gardens